Implementation of Technology Transfer Based on Law No. 25 of 2007 on Investment in the Context of Development of Industry in Indonesia - Luthfi, A Hashbi (Walisongo Law Review (Walrev), 2019)
Legal arrangements in the field of technology transfer related to foreign investment need to be considered in order for the entry of new technology in Indonesia. This article aims to know how the implementation of Technology Transfer under Law No. 25 of 2007 on Investment in Indonesia and Transfer of technology developments in Indonesia with the Law No. 25 Year 2007 on Investment. The method used is a normative juridical analytical descriptive, whereas in analyzing the data using qualitative methods and presented descriptively. From this study shows that the main problem at the root problem of transfer of technology in Indonesia is the law governing the transfer of technology itself. That's because there is no obvious technical regulations regarding foreign investment for technology transfer in the discourse of transfer of technology as stipulated in Law No. 25 of 2007 on Investment is only optional and not become an obligation for foreign investors to come. It was concluded that the concept of technology transfer in foreign investment in Indonesia is based on the principle of self-reliance, development Technology transfer through foreign investment in Indonesia has not had a clear regulation so here said technology transfer is only seen as a choice for investors not as a an obligation which is binding and accompanied with strict punishment. Pengaturan hukum di bidang alih teknologi yang terkait dengan investasi asing perlu dipertimbangkan untuk masuknya teknologi baru di Indonesia. Artikel ini bertujuan untuk mengetahui bagaimana implementasi transfer teknologi berdasarkan UU No. 25 tahun 2007 tentang Investasi di Indonesia dan transfer perkembangan teknologi di Indonesia dengan UU No. 25 Tahun 2007 tentang Investasi. Metode yang digunakan adalah deskriptif analitik yuridis normatif, sedangkan dalam menganalisis data menggunakan metode kualitatif dan disajikan secara deskriptif. Dari penelitian ini menunjukkan bahwa masalah utama pada akar masalah transfer teknologi di Indonesia adalah hukum yang mengatur transfer teknologi itu sendiri. Itu karena tidak ada peraturan teknis yang jelas mengenai investasi asing untuk transfer teknologi dalam wacana transfer teknologi sebagaimana diatur dalam Undang-Undang Nomor 25 Tahun 2007 tentang Investasi hanya opsional dan tidak menjadi kewajiban bagi investor asing untuk datang. Dapat disimpulkan bahwa konsep alih teknologi dalam investasi asing di Indonesia didasarkan pada prinsip kemandirian, pengembangan Transfer teknologi melalui investasi asing di Indonesia belum memiliki regulasi yang jelas sehingga disini dikatakan transfer teknologi hanya dipandang sebagai pilihan bagi investor bukan sebagai kewajiban yang mengikat dan disertai dengan sanksi tegas.